A Novel Digital Watermarking Approach for Accurate Authentication Using of Integer Wavelet Transform Coefficients (International Journal of Engineering and Computer Science, 2016)
The prominence of digital image processing domain has been increased from last few decades due to its advanced research areas such as medicine, biometrics, military, robotics etc. In this work an important issue has taken as area of research i.e. protecting the privacy information from the unauthenticated users either as accidental or incidental ways. Although tremendous progress has been made in the past years but still protecting the privacy information is concerned area in the field of security. A novel image authentication scheme for gray scale images are implemented in this work and the process of the embedding digital watermark is carried by performing the quantization process on the image. The novel things implemented in the proposed work is detection of tampered parts of the image and to detect minute modification of an image and to embed the watermark mid frequency band of a second level DWT transform was used. An approximation of the original image based on LL band was stored as a recovery mark for restoration of the image. Watermarked image has achieved a good PSNR value of 40 dB compared to original cover image. Restored image quality was also very good with a PSNR of more than 35 dB compared to unmodified watermarked image even when 25% of the received image is cropped. Finally the simulation results reveals that the proposed method provides the reliable balance between fidelity of the watermarked image and the quality of the restored image.